Interaction of a pyrene derivative with cationic [60]fullerene in phospholipid membranes and its effects on photodynamic actions - Takagi, Hayato; Çelik, Çetin; Fukuda, Ryosuke; Guo, Qi; Higashino, Tomohiro; Imahori, Hiroshi; Yamakoshi, Yoko; Murakami, Tatsuya (Beilstein Journal of Organic Chemistry, 2024)
We have reported that upon visible light irradiation, ferrocene-porphyrin-[60]fullerene triad molecules yield long-lived charge-separated states, enabling the control of the plasma membrane potential (Vm) in living cells. These previous studies indicated that the localization of the triad molecules in a specific intra-membrane orientation and the suppression of the photodynamic actions of the [60]fullerene (C60) moiety are likely important to achieve fast and safe control of Vm, respectively. In this study, by mimicking our previous system of triad molecules and living cells, we report a simplified model system with a cationic C60 derivative (catC60) and a liposome with embedded 1-pyrenebutyric acid (PyBA) to demonstrate that the addition of PyBA was important to achieve fast and safer control of Vm.
Keywords: liposome; π–π interaction; reactive oxygen species; superoxide radical anion